2′-Fucosyllactose as a prebiotic modulates the probiotic responses of Bifidobacterium bifidum - Jingfang Du; Hong Yang (Current Research in Food Science)
2′-Fucosyllactose (2′-FL), one of the most representative oligosaccharides in human milk, is intimately linked to the enrichment of specific Bifidobacterium species. However, the efficacy of 2′-FL in modulating the probiotic responses of bifidobacterium has been rarely researched. Thereinto, three key issues have yet to be reported: the effects of 2′-FL hydrolysis on bifidobacterial growth, the protective effects of 2′-FL on bifidobacterium under gastrointestinal stress and the inhibitory activity of 2′-FL metabolites against Cronobacter spp. This work intended to address these concerns. 2′-FL dramatically accelerated the growth and proliferation of Bifidobacterium bifidum YH17 and Bifidobacterium bifidum BBI01. The glucose in lactose core on 2′-FL was preferable for B. bifidum to achieve substantial increases in biomass while the galactose was not readily available. Additionally, 2′-FL showed unique advantages in ameliorating the resistance of B. bifidum to gastrointestinal challenges. 2′-FL considerably improved the adhesive property of B. bifidum, thus facilitating the competitive elimination of Cronobacter sakazakii ATCC 29544 and Cronobacter muytjensii ATCC 51329 by B. bifidum. The growth inhibition of 2′-FL on the Cronobacter strains was mediated by promoting the secretion of antibacterial substances from B. bifidum. The inhibitory activity hinged on the B. bifidum strains. 2′-FL specifically induced B. bifidum BBI01 to produce some antibacterial substances that were proteinaceous, thermostable and relatively stable even at pH 8.0. These antibacterial substances played a key role in the inhibitory activity and had a synergistic effect with acidification. These observations provide a useful guideline for developing synbiotic supplements to intervene the infant gut microbiota.